A3_3_Detection bias in the search for extrasolar planets_v2 - Littlejohns, Owen; Hill, Kathryn; Laird, Ryan (Physics Special Topics, 2009)
The detection of extra solar planets is discussed, with particular emphasis laid upon the radial velocity method. An expression for how detectable a planet is based on planetary mass is derived. To illustrate the difficulties in finding terrestrial planets, this formula is applied to the Earth-Sun system to find the fractional change in wavelength and shown to require a sensitivity approximately 103 times more sensitive than that needed to detect Hot Jupiters.